Analisis Kebutuhan Pengembangan Blended Learning Terintegrasi Strategi PBLRQA (Problem-Based Learning and Reading, Questioning & Answering) pada Pembelajaran Biologi - Hasmunarti, Hasmunarti; Bahri, Arsad; Idris, Irma Suryani (Biology Teaching and Learning, 2018)
Abstract.Â  Global demands require the world of education to always adjust technological developments towards efforts to improve the quality of education. This study aims to determine the potential and needs of lecturers and students in biology classroom, which will be used as a base in the development of blended learning integrated with PBLRQA strategy (Problem-Based Learning and Reading, Questioning & Answering) on biology classroom. This research was a descriptive research. The results of this study showed that lecturers and students need a learning environment that integrates technology in learning, allowing students to communicate and obtain information from various sources. The use of technology in learning with blended learning integrated with PBLRQA strategy can create the learning environment more effective, efficient, and interesting, suitable with students' interest in the use of interactive media such as laptops and smartphones. By using technology, abstract material in biology can be more easily understood and problems related to biological learning expected to be resolved. Keywords: blended learning, PBLRQA, flipped class, biology learning.